Existence of Multiple Solutions for Second-Order Problem with Stieltjes Integral Boundary Condition - Hu, Qing-Qing; Yan, Baoqiang (Journal of function spaces, 2021)
In this paper, we consider the existence of multiple solutions for second-order equation with Stieltjes integral boundary condition using the three-critical-point theorem and variational method. Firstly, a novel space is established and proved to be Hilbert one. Secondly, based on the above work, we obtain the existence of multiple solutions for our problem. Finally, in order to illustrate the effectiveness of our problem better, the example is listed.